Parameterized complex dielectric functions of CuIn1−xGaxSe2: applications in optical characterization of compositional non‐uniformities and depth profiles in materials and solar cells. (23rd April 2016) - Aryal, Puruswottam; Ibdah, Abdel‐Rahman; Pradhan, Puja; Attygalle, Dinesh; Koirala, Prakash; Podraza, Nikolas J.; Marsillac, Sylvain; Collins, Robert W.; Li, Jian
Abstract: In‐situ spectroscopic ellipsometry (SE) was employed to extract the complex dielectric functions ε = ε1  + iε2 over the spectral range of 0.75–6.5 eV for a set of polycrystalline CuIn1− x Ga x Se2 (CIGS) thin films with different alloy compositions x  = [Ga]/{[In] + [Ga]}. For highest possible accuracy in ε for each CIGS thin film, specialized SE procedures were adopted including (i) deposition to a thickness of ~600 Å on smooth native oxide covered crystal silicon wafers, which minimizes the surface roughness on the film and thus the required corrections in data analysis, and (ii) measurement in‐situ, which minimizes ambient contamination and oxidation of the film surface. Assuming an analytical form for each of the ε spectra for these CIGS films, oscillator parameters were obtained in best fits, and these parameters were fit in turn to polynomials in x . With the resulting database of polynomial coefficients, the ε spectra for any composition of CIGS can be generated from the single parameter, x . In addition to enabling accurate contactless determination of bulk and surface roughness layer thicknesses of CIGS films by high speed multichannel SE, the database enables characterization of the composition and its profile with depth into these films, and even how the depth profile varies spatially within the plane of the films. In this study, depth profile parameters were found to correlate spatially with solar cell performance parameters. As a result, SE provides the capability of contactless compositional analysis of production‐scale CIGS photovoltaic modules at high speed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Dielectric function spectra for thin Cu(In1−x Gax )Se2 (CIGS) with different Ga contents x were determined using in‐situ spectroscopic ellipsometry (SE), and were parameterized analytically as functions of a single parameter, x . SE analyses of non‐uniformities in x were consistent with EDX and AES characterizations. From the correlations between the analysis results of mapping SE and cell performance parameters, controlling factors for Jsc, efficiency, and Voc were identified for high efficiency thin (0.7 micron) CIGS cells, leading to an SE‐guided optimization pathway.